KORELASI ANTIGEN NS1 KUANTITATIF TERHADAP DERAJAT KEPARAHAN INFEKSI DENGUE - , Ni Made Adi Purnami, Prof. dr. Mohammad Juffrie, Ph.D, Sp.A(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Dengue infection is one of the main causes of morbidity and mortality of children in Indonesia. Since it is known that earlier treatment and supportive therapies can decreased case fatality rate from DHF, identification of the person who has risk to develop to DHF must be quickly found mainly in areas of endemic. The purpose of these studies is to find a correlation between increase of quantitative sNS with clinical history of severe dengue infection, and also to determine the cutt off point of quantitative sNS1 with the probability severe dengue infection. This research is a cross-sectional study conducted on children with dengue infection in Tropical Infections Division of The children's Health Department, Denpasar. Detection of the antigen is made by examining sNS1 immuno-assay. Analysis correlation of Spearman test used to look the relationship between increased quantitative sNS1 with clinical history of severe dengue. ROC curve and the AUC used to determine the cutt off point of quantitative sNS1 with the probability severe dengue infection. This research found a strong positive relationship between sNS1and clinical history of severe dengue with a value of r = 0.903, p<0.001. Spearman analysis showed that increased sNS1 have positive correlation with severe dengue infection.